Business excellence: the managerial and value-creation efficiencies of the insurance companies - Nourani M.; Devadason E.S.; Kweh Q.L.; Lu W.-M. (Routledge, 2023)
The competitive global environment today has brought with it profound challenges, leading to excessive risk-taking behaviour by insurance companies. These companies require retaining their performance at high levels, while dealing with risk-taking behaviour. Following this, performance evaluation has emerged as a fundamental building block of total quality management and business excellence for an organisation. Hence, this paper aims to decompose the overall performance of an insurer into two efficiency components, managerial efficiency and value-creation efficiency, where risk management activities are embedded in the efficiency evaluation. This paper applies a network data envelopment analysis model to evaluate the performance of 30 Malaysian insurers for the period 20082012. The performance analysis indicates that the average overall efficiency of the insurance sector in Malaysia was approximately 63.5%, largely attributed to value-creation efficiency. The frontier projection analysis reveals that Malaysian insurers should enhance their managerial ability by substantially reducing their input quantities. Finally, through a managerial decision-making matrix, only nine insurers are classified as having high levels of both managerial and value-creation efficiencies. Significant differences in managerial efficiency and value-creation efficiency among insurers suggest that decision-makers in insurance companies of Malaysia seem to have directed resources to address the specific inefficiency types. 2016 Informa UK Limited, trading as Taylor & Francis Group.